1997
DOI: 10.1021/bi9704109
|View full text |Cite
|
Sign up to set email alerts
|

Oligomycin Sensitivity Conferring Protein (OSCP) of Bovine Heart Mitochondrial ATP Synthase:  High-Affinity OSCP−Fo Interactions Require a Local α-Helix at the C-Terminal End of the Subunit

Abstract: Earlier studies on oligomycin sensitivity conferring protein (OSCP) of bovine mitochondrial ATP synthase (F1Fo) indicated that a deletion mutant form (CD-10), lacking the last 10 amino acid residues (K181-L190), was unable to bind to the Fo segment, or reconstitute energy-linked reactions in OSCP-depleted F1Fo complexes [Joshi et al. (1996) Biochemistry 35, 12094-12103]. So far as known, the K181-L190 region of all mammalian species of OSCP harbors four charged residues at positions 181, 184, 187, and 188, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Together these subunits are believed to form a "second stalk" reaching from the membrane to near the top of the F 1 sector, which may function to hold the ␣ 3 ␤ 3 subunits stationary during rotation of ␥ and ⑀ driven by proton flow through F 0 (48,49). Earlier truncation and mutagenesis studies showed that the C terminus of b was essential for proper assembly of ATP synthase (10) and implied that the C terminus of ␦ played a role in interaction of F 1 with the F 0 sector (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together these subunits are believed to form a "second stalk" reaching from the membrane to near the top of the F 1 sector, which may function to hold the ␣ 3 ␤ 3 subunits stationary during rotation of ␥ and ⑀ driven by proton flow through F 0 (48,49). Earlier truncation and mutagenesis studies showed that the C terminus of b was essential for proper assembly of ATP synthase (10) and implied that the C terminus of ␦ played a role in interaction of F 1 with the F 0 sector (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Membranes of mutant E. coli strains expressing truncated forms of ␦ showed little ATPase activity (21), suggesting that F 1 cannot bind to the membrane in the absence of ␦. In truncation and mutagenesis studies using the mitochondrial (22,23) and yeast (24) homologues of ␦, called OSCP 1 for oligomycin sensitivity conferring protein, the C-terminal region of OSCP was implicated in F 0 binding.…”
mentioning
confidence: 99%
“…, in the coupled enzyme [70]. In this context, depletion/reconstitution studies in isolated membranes demonstrated that OSCP is absolutely necessary in coupling proton translocation to ATP synthesis [71]. In keeping with this key function of the subunit, yeast OSCP knockouts failed to survive under normal growth conditions [73].…”
Section: Oscp: Location and Structurementioning
confidence: 99%
“…Fragments of subunit b and the OSCP with intact C-terminal regions form somewhat unstable heterodimeric complexes that are stabilized by F 6 . Deletion of residues 185-214 of subunit b prevents any association between the OSCP and the rest of the stator (6), and deletion of the C-terminal region of the yeast OSCP uncouples pmf partially from ATP synthesis (14). Also, biotin attached to the C-terminus of the yeast OSCP was detected at the junction between the crown and the nucleotide binding domains of F 1 (15), which is consistent with the position of the C-terminal region of the OSCP in the bovine F 1 -stator T complex.…”
Section: *R Merge ϭ ͚H͚i͉i(h) ϫ I(h)i͉/͚h͚ii(h)i Where I(h) Is the Mmentioning
confidence: 99%